ULTRASTRUCTURE OF THE ENDOSYMBIOTIC DINOFLAGELLATE Symbiodinium microadriaticum LIVING IN THE SEA ANEMONE Anemonia viridis - Suharsono, - (Marine Research in Indonesia, 1992)
The zooxanthella, Symbiodinum microadriaticum, an endosymbiotic dinoflagellate shows variation in its ultrastructure within its population in the sea anemone, Anemonia viridis. Such variation included the number of thylakoid, the structure of inclusions and the structure of amphiesma. The string-like structure was also found in the nucleoplasm. Some zooxanthellae have a branching or double pyrenoid with two or three stalks. Under certain condition, which are not clearly understood, two or three zooxanthellae are enclosed within one very thick membrane.